PERANAN BUAH MENGKUDU (Morinda citrifolia) TERHADAP AKTIVITAS FAGOSITOSIS LEUKOSIT POLIMORFONUKLEAR TIKUS (Rattus noroegicus) YANG DIBERI DIET LEMAK TINGGI The Effect of Mengkudu (Morinda dtrifolia Linn.) to The Phagocytose Activity of Polymorphonuclear L - Jemmi Setio Utomo; Rinto Sukoco; Adimas Galih; Siti Isrina Oktavia Salasia (State Islamic University of Sultan Syarif Kasim Riau, 2006)
This study was done to evaluate the effect of mengkudu (Morinda citrifolia Linn.) to the phagocytose activity of polymorphonuclear leucocytes of high dietary fat of ram.Fifteen female Wistar albino ram (Rattus noroegicus) 1 month of age, were divided into 5 groups of 3 rats. The 1st group was fed with the basic food as a control. The 2N:1 group was fed with the basic food and 5% of fat The 3rd, 4111, and 5111 groups were fed with the basic food and 5% fat suplemented with mengkudu with the dose of 3,2 rot, 3,6 m1, and 4,0 ml/200 g body weight! oral/day for 2 months, respectively. At the end of the reasearch, the blood samples were collected from retroorbital plexus to evaluate the phagocytose activity of polymorphonuclear leucocytes in vitro. .The resulm of the reasearch were shown that the 5% diet fat of rats did not influence the phagocytose activity of polymorphonuclear leucocytes in vitro (22,13±1,33 bacteria/cell) compared to the control (21,11%3,59 bacteria/cell). Mengkudu with the dose of 3,6 ml/200 g body weight could increase the phagocytose activity of polymorphonuclear leucocytes (27,69%2,99 bacteria/cell) significantly (p<O,05) compared to the control (21,11%3,59 bacteria/cell) and the grouJ! hichfed the basic food and 5% of fat (22.13±1,33 bacterialcell).